Between two worlds: Baroque spectacle and enlightenment thought in the autos sacramentales by Sor Juana Inés de la Cruz (1648-1695) - Brooke, A (2012)
This thesis is the first book-length study of the three autos sacramentales by Sor Juana Inés de la Cruz. Sor Juana’s religious drama has received little attention, despite her status as one of the greatest figures of Mexican literature. She was also writing during a particularly significant period in Hispanic literary history: at the end of the Spanish Golden Age, and at the rise of a new class of intellectual élites in the New World, the criollos. I contend that Sor Juana’s autos sacramentales are crucial to understanding how she contributed to the formation of a criollo identity. In doing so, she engaged with the mentalities of two continents and two historical periods: Europe and the Americas, and the Baroque and the Enlightenment. To demonstrate this, I provide a study of each of Sor Juana’s sacramental plays, alongside the loa which was written to accompany them. My method combines close-text reading with a historical approach, and I pay particular attention to the theological function of the plays. In each chapter, I focus on the concurrent strands of thought in her works. I consider how the plays demonstrate the Catholic doctrine of transubstantiation, and how they engage with the aesthetic and theological mindset of the Spanish Baroque. I study how they incorporate indigenous Nahuatl theatrical traditions, and ask how they engage with the scientific developments of the Enlightenment. I conclude that in her autos sacramentales Sor Juana expresses a mindset that is both geographically and historically “between two worlds.” The influence of Nahuatl theatre on Sor Juana’s dramaturgy has never before been studied. The influence of Enlightenment thought on her works has been noted by a few scholars, but never considered in relation to her religious works. The demonstration of the interaction of Enlightenment and Catholic ideas challenges our notion of the Enlightenment as a secularising movement, and has potential implications for scholars of the period beyond the sphere of Sor Juana studies.